High-Throughput Drug Screening System Based on Human Induced Pluripotent Stem Cell-Derived Atrial Myocytes ∼ A Novel Platform to Detect Cardiac Toxicity for Atrial Arrhythmias - Honda, Yayoi; Li, Jun; Hino, Aya; Tsujimoto, Shinji; Lee, Jong-Kook (Frontiers in Pharmacology, 2021)
Evaluation of proarrhythmic properties is critical for drug discovery. In particular, QT prolongation in electrocardiograms has been utilized as a surrogate marker in many evaluation systems to assess the risk of torsade de pointes (TdP) and lethal ventricular arrhythmia. Recently, new evaluation systems based on human iPS cell-derived cardiomyocytes have been established. On the other hand, in clinical situations, it has been reported that the incidence of atrial arrhythmias such as atrial fibrillation has been increasing every year, with the prediction of a persistent increase in the near future. As to the increased incidence of atrial arrhythmias, in addition to the increased population of geriatric patients, a wide variety of drug treatments may be related, as an experimental method to detect drug-induced atrial arrhythmia has not been established so far. In the present study, we characterized the atrial-like cardiomyocytes derived from human induced pluripotent stem (iPS) cells and examined their potential for the evaluation of drug-induced atrial arrhythmia. Atrial-like cardiomyocytes were induced by adding retinoic acid (RA) during the process of myocardial differentiation, and their characteristics were compared to those of RA-free cardiomyocytes. Using gene expression and membrane potential analysis, it was confirmed that the cells with or without RA treatment have atrial or ventricular like cardiomyocytes, respectively. Using the ultra-rapid activating delayed rectifier potassium current (IKur) channel inhibitor, which is specific to atrial cardiomyocytes, Pulse width duration (PWD) 30cF prolongation was confirmed only in atrial-like cardiomyocytes. In addition, ventricular like cardiomyocytes exhibited an early after depolarization (EAD) by treatment with rapidly activating delayed rectifier potassium current (IKr) channel inhibitor, which induces ventricular arrhythmia in clinical situations. Here, we have established a high-throughput drug evaluation system using human iPS cell-derived atrial-like cardiomyocytes. Based on the obtained data, the system might be a valuable platform to detect potential risks for drug-induced atrial arrhythmias.